CHANGES IN THE MUCOSE OF UPPER GASTROINTESTINAL TRACT IN CORONARY HEART DISEASE - B. M. Magomedova; K. G. Glebov; N. V. Teplova; A. E. Kotovsky; N. G. Artamonova (Кардиоваскулярная терапия и профилактика, 2017)
Aim. To assess the specifics of endoscopy presentation of mucosal lesions of upper gastrointestinal tract (UGIT) in patients with chronic coronary heart disease (CCHD) with no rhythm disorders and with atrial fibrillation (AF).Material and methods. Esophagogastroduodenoscopy was done in 100 CCHD patients. All patients were selected to 2 groups comparable by age and gender. First group (n=50) included CCHD patients, the second (n=50) — CCHD with AF. The investigations were performed with videoendoscopic equipment byOLYMPUS systemic videocenters CV-150 and CV-180 EVIS EXERA II.Results. Evaluating the results of endoscopy, in all 100 patients there were various changes of the mucose of UGIT. No statistically significant differences found, however in CCHD group with rhythm disorder there was noted slight predominance of patients with superficial gastritis, as erosions in anthral part of the stomach. One of explanation of the erosions is due to excessive drug intake per os, that could influence the mucose of UGIT.Conclusion. All CCHD patients, who have been prescribed the therapy for main disease, are in need for preventive intake of the drugs protecting UGIT.